Functional markers, sub-genomic selection patterns and haplotype regions associated with seed glucosinolates and chlorophyll content in rapeseed (Brassica napus L.) - Qian, Lunwen; Justus Liebig University Giessen (My University, 2016)
Brassica napus (rapeseed, oilseed rape, canola) is the second most important oilseed crop in the world after soybean. Worldwide production of rapeseed was 61 million metric tons (MT) in 2011. Brassica napus (2n=38, AACC) is derived from interspecific hybridisation events between B. rapa (2n=20, AA) and B. oleracea (2n=18, CC), and was probably selected as an oilseed crop only 300-400 years ago. Oilseed producing B. napus has only achieved economic importance in the past forty years following an intensive breeding programme to decrease nutritionally undesirable components of the oil and meal, and to increase yields. In some areas, rapeseed, which contains more than 40 % oil, has become more profitable than soybeans, which contain about 18 % oil. Attention of breeders was initially focused on reducing levels of erucic acid in the oil and glucosinolate (GSL) content in the meal. Four major quantitative trait locus (QTL) regions on chromosomes A09, C02, C07 and C09 relate to reduction in seed GSL content which has been achieved in worldwide rapeseed breeding during the past three decades. On the other hand, further reductions in seed GSL require the combination of these main effect loci with additional QTL that have less prominent effects. Such loci are often overlooked in genetic mapping studies that use parents carrying main-effect loci, making it difficult to implement them into breeding programmes. In this thesis, 43 QTL for seed GSL content were dissected over multiple environments in a doubled haploid (DH) population derived from two low-GSL parents. Two cleaved amplified polymorphic site markers were developed from within the confidence intervals of the detected QTL regions. These markers ware specific for B. napus orthologues of the glucosinolate biosynthesis genes IPMDH1 and APR3 and segregation of the marker alleles are explaining 3-8 % of the phenotypic variation for seed GSL. The use of these markers in marker-assisted breeding will facilitate breeding for ultra-low seed GSL content in canola.Rapeseed is grown in different geographical regions of the world. It is adapted to different environments by modification of flowering time. Different B. napus gene populations have undergone strict selection for flowering-related traits, including vernalisation requirement, winter survival and photoperiod-dependant flowering. Also they have undergone strict selection for essential seed quality traits (primarily low erucic acid and GSL contents). Chinese semi-winter rapeseed breeding has extensively used diploid Brassica species, particularly B. rapa, to enrich the genetic potential of the local gene pool. High-resolution genome analysis technologies provide an unprecedented level of insight into structural diversity across crop genomes. In this thesis, a high-density 60k Single Nucleotide Polymorphism (SNP) array is used to analyze linkage disequilibrium (LD) and haplotype structures in homologues QTL regions for erucic acid and GSL contents within the A- and C- subgenomes of 203 Chinese semi-winter rapeseed inbred lines. The result shows a strong selection of large chromosome regions associated with these important rapeseed seed quality traits conferred by C-subgenome QTL. This implies that an increase in genetic diversity and recombination within the C-genome is particularly important for breeding. The resolution of genome-wide association studies (GWAS) is also expected to vary greatly across different genomic regions.GWAS examines co-transmission of phenotypes with genetic markers that provide a powerful insight into correlations of haplotype diversity to phenotype groups. Analysis of gene content in conserved haplotype blocks can further provide insight into co-selection for different quantitatively inherited traits. In this thesis a genome-wide analysis of haplotypes associated with the important physiological and agronomic traits leaf chlorophyll and seed GSL content was performed. Analysis of homologous haplotypes on chromosomes A05 and C05 revealed multiple orthologous copies of the chloroplast membrane protein gene PALMITOYL-MONOGALACTOSYLDIACYLGLYCEROL DELTA-7 DESATURASE (FAD5) associated with leaf chlorophyll content. Conserved haplotype blocks on chromosome A02 contained a number of genes related to chlorophyll synthesis or degradation. The multigene haplogroup had a significantly greater contribution to variation for leaf chlorophyll content than the haplogroups for any single gene. Furthermore, conserved haplotypes on chromosome A01 were observed to show opposite effects on leaf chlorophyll content and seed GSL content. Haplotype network analysis across these four haplotype regions showed introgression from winter rapeseed contributing to genetic diversity and to higher chlorophyll content.
Keywords: ddc:630